Enhanced catalytic performance of Cu/Ag/CeO2 catalyst for the SCR of NO by propylene - Nor Aishah Saidina Amin; Chong, Chee Ming; Symposium of Malaysian Chemical Engineers (18th. : 2004 : Perak) (Skudai : Universiti Teknologi Malaysia, 2004)
50